Complexity estimates depending on condition and round-off error. - Cucker, Felipe
This paper has two agendas. One is to develop the foundations of round-off in computation. The other is to describe an algorithm for deciding feasibility for polynomial systems of equations and inequalities together with its complexity analysis and its round-off properties. Each role reinforces the other.
Keywords: Theory of computation; Analysis of algorithms and problem complexity; Mathematics of computing; Numerical analysis; Algorithms; Theory